Influence of Soil Depth on Sorption and Desorption Processes of Hexazinone - CHITOLINA,G.M. (2020)
ABSTRACT: Herbicides with a high leaching capacity, such as hexazinone, tend to reach deeper soils more easily, where retention of the product affects its availability in the soil solution. Therefore, it is important to understand the behavior of hexazinone at a variety of soil depths. The objective of this research was to evaluate the sorption and desorption of hexazinone throughout the soil profile. The sorption and desorption processes of 14C-hexazinone [triazine-6-14C] at three soil depths (0-10, 10-20, and 20-30 cm) were evaluated by the equilibrium batch method, and the radioactivity of the herbicide was quantified by liquid scintillation spectrometry. Five different concentrations of hexazinone (0.12, 0.19, 0.25, 0.31, and 0.38 µg mL-1) in a methanol solvent were used. The concentrations of the herbicide in equilibrium and sorbed in the soil were adjusted by using isotherms according to the Linear, Freundlich, and Langmuir models. Hexazinone sorption at soil depths of 0-10, 10-20, and 20-30 cm showed decreasing Freundlich coefficients (Kf) with values of 0.18, 0.11, and 0.08 g (1-1/n) L1/n kg-1 (50.49, 47.58, and 46.37% sorbed), and in the desorption the Kf were 7.96, 7.93, and 9.82 g (1-1/n) L1/n kg-1 (26.17, 26.58, and 28.68% desorbed), respectively. The small difference in organic carbon content between soil depths was sufficient to affect hexazinone retention, interfering with the bioavailability of this product in the soil solution for weed control.